Effects of Multi Amide Compound Nucleating Agent on Non-isothermal Crystallization of Semi-aromatic Polyamide 6T/6 - Zhang, Shengchun; Han, Bing; Feng, Zhiming; Zhang, Chunxiang; Zhang, Kejie; Ying, Sanjiu (Asian Journal of Chemistry, 2013)
The influence of multi amide compound nucleating agent TMC-328 on the nonisothermal crystallization behaviour of the semi-aromatic polyamide 6T/6(PA6T/6) is investigated. It is observed that the crystallization peak temperature (Tp) of PA6T/6-TMC328 is marginally higher than neat PA6T/6 at various cooling rates. Furthermore, the half-time for crystallization (t1/2) decreased with in TMC-328, implying the nucleating role of TMC-328. The nonisothermal crystallization data is analyzed using Avrami and Combined Ozawa-Avrami method. The validity of kinetic models on the nonisothermal crystallization process of PA6T/6-TMC328 is described. The activation energy for nonisothermal crystallization of neat PA6T/6 and PA6T/6s with contents of TMC-328 based on Kissinger method is evaluated.